Penyensoran dan Pelarangan Buku serta Implementasinya di Indonesia - Rodin, Rhoni; Rosaliya, Mela; Oktavia, Media; Amrullah, Abdul Karim (Universitas Islam Negeri Sumatera Utara, 2024)
Censorship and book banning is a complex and sensitive issue in many countries, including Indonesia. This practice has a long history, closely linked to political and social dynamics. In the Indonesian context, censorship and book banning did not only occur during the New Order era, but also continued into the Reformation era. This paper aims to review the history, regulations and implementation of censorship and book banning in Indonesia, as well as its impact on freedom of expression and public literacy. This research uses the literature review method which is an important part of the research that we carry out. Literature review is also called literature review, or literature review. The long history of censorship from the colonial to post-reform eras shows that this policy was often influenced by changing political and social contexts. Despite efforts to protect public order and societal values, censorship also has a negative impact on freedom of expression and literacy. It is important for Indonesia to continue to strive for a balance between maintaining social stability and respecting the right to freedom of expression of its citizens.